Physics ContributionsDosimetric evaluation of internal shielding in a High Dose Rate skin applicator - Lliso, Françoise; Granero, Domingo; Perez-Calatayud, Jose; Carmona, Vicente; Pujades, M Carmen; Ballester, Facundo (Journal of Contemporary Brachytherapy, 2011)
Purpose : The Valencia HDR applicators are accessories of the microSelectron HDR afterloading system (Nucletron) shaped as truncated cones. The base of the cone is either 2 or 3 cm diameter. They are intended to treat skin lesions, being the typical prescription depth 3 mm. In patients with eyelid lesions, an internal shielding is very useful to reduce the dose to the ocular globe. The purpose of this work was to evaluate the dose enhancement from potential backscatter and electron contamination due to the shielding. Material and methods : Two methods were used: a) Monte Carlo simulation, performed with the GEANT4 code, 2 cm Valencia applicator was placed on the surface of a water phantom in which 2 mm lead slab was located at 3 mm depth; b) radiochromic EBT films, used to verify the Monte Carlo results, positioning the films at 1.5, 3, 5 and 7 mm depth, inside the phantom. Two irradiations, with and without the lead shielding slab, were carried out. Results : The Monte Carlo results showed that due to the backscatter component from the lead, the dose level raised to about 200% with a depth range of 0.5 mm. Under the lead the dose level was enhanced to about 130% with a depth range of 1 mm. Two millimeters of lead reduce the dose under the slab with about 60%. These results agree with film measurements within uncertainties. Conclusions : In conclusion, the use of 2 mm internal lead shielding in eyelid skin treatments with the Valencia applicators were evaluated using MC methods and EBT film dosimetry. The minimum bolus thickness that was needed above and below the shielding was 0.5 mm and 1 mm respectively, and the shielding reduced the absorbed dose delivered to the ocular globe by about 60%